Review of municipal solid waste management options in Malaysia, with an emphasis on sustainable waste-to-energy options - Aja, O.C. (Springer Japan, 2014)
A beautiful and clean environment is the desire of every society. Malaysia is facing an uncontrolled increase in municipal solid waste (MSW) generation due to population growth, economic advancement, and industrialization, but the current, most common waste disposal practice of landfilling is not sustainable. The increasing standard of living also saps more energy from the power generation systems in which fossil fuels are the major source of fuel for the plants. Malaysia generates about 0.5â1.9Â kg/capita/day of MSW; a total of about 25,000Â tonnes/day of MSW is currently generated and is estimated to exceed 30,000Â tonnes/day by 2020. Malaysian MSW is mainly composed of 45Â food waste, 24Â plastic, 7Â paper materials, 6Â metal, 4Â wood and 3Â glass, which are commingled, and is thus characterised by 52â66Â moisture content. Currently, 80â95Â of collected MSW is landfilled and 5Â is recycled, while composting and energy recovery are rarely practiced. This paper reviews the solid waste practice in Malaysia and looks into alternative management options for sustainability. Malaysia MSW represents recyclable power and energy potential if properly sorted. This study considered the practice of sorting at the source and the use of combustible MSW components as fuel to generate heat for a hybrid solar, flue gas, chimney power plant. Â© 2013, Springer Japan.